Default, mortgage standards and housing liquidity - Allen Charles Head; Hongfei Sun; Chenggang Zhou (Queen's University, Department of Economics, 2016)
The effects of households' indebtedness on their house-selling decisions are studied in a dynamic equilibrium model with search in the housing market and defaultable long-term mortgages. In equilibrium, both sellers' asking prices and time-to-sell increase with the relative size of their outstanding mortgages. In turn, the liquidity of the housing market associated with time-to-sell determines the mortgage standards of competitive lenders, measured by the maximum loan-to-value (LTV) ratio offered at origination. Calibrated to the U.S. economy, the model generates, as observed, positive correlations over time between house prices and LTV's at origination and across sellers among asking prices, time-to-sell, and LTV's outstanding.
Keywords: E30; G21; R10; R31; 330; Housing; Mortgages; Foreclosures; Directed Search; Liquidity; Block Recursive Equilibrium